Educação e democracia : experiências escolares dissidentes na encruzilhada das reformas educativas e da exclusão social - Fernández, Silvina Julia (2007)
This work aims to understand the various process and factors confluent in the school quotidian, that facilitate the emergence, consolidation, continuation and declination of dissidents school experiences. Experiences that, accentuating their educational function, can realize another ways to be in the school (and, whit this, in the society, in the word...) that contradict and question the modern School statement. Statement that it pretends unique, which principal postulates were affirmed by the educational politics, in the lasts decades, configuring situations that conspires against the survival of that dissidents experiences. Experiences understood as dissidents statements that could survive along the time (in one case studied, along decades...) in the educational system field. Process and factors studied (specially, through the oral history) in four participant schools two argentine and two brazilian that, beyond their differences, shared the experience of being dissidents schools, demonstrating, one more time, that another schools are possible.